KUALITAS HIDUP MANTAN PECANDU NARKOBA YANG SEDANG MENJALANI TERAPI METADON - Gede Indra Surya Lasmawan; Tience Debora Valentina (Jurnal Psikologi Udayana, 2015)
Over time, drugs abuse in various parts of the world increase widely. Similarly in Indonesia, the results of a survey conducted by the National Narcotics Agency revealed that there are 3.8 million people in Indonesia are drugs user in 2013. Various cases showed that the impact of drugs abuse seen in the loss of materials and non-materials, and can even cause death. Therefore, people who addicted to drugs should immediately stop consuming and required to undergo a recovery process. Therapeutic method with medical approaches recognized until now are diversion programs to substitute drugs or other substance called methadone therapy (Puspita, 2008). Although there are many positive benefits that make the patient to function normally, but methadone therapy also cause side effects and dependence that can psychologically affect the quality of life of patients (Maeyer, 2011). This makes the researcher interested in studying the quality of life of former drugs addicts undergo methadone treatment. This study used a qualitative method with a phenomenological design with interview and observation as data collection techniques. Respondents were four patients who involve in methadone therapy. Results of the study shows that methadone helps individuals in various aspects of quality of life such as physical health aspect, where the individual can return to normal activities. In the psychological aspects, the individual has motivation to reach higher accomplishment and not mired in regret. Relate to aspects of social relations, family members give support and motivation. Furthermore, environmental aspect showed that individuals have their own work to fulfill their necessary. Keywords: quality of life, former drugs addicts, methadone therapy